Career Search Efficacy and Student Life Satisfaction among Vocational School Students: The Mediating Role of Career Decision Self-Efficacy - Asriyana; DYP. Sugiharto; Sunawan Sunawan; Heru Mugiarso (Universitas PGRI Yogyakarta, 2026)
This study investigates the relationship between career search self-efficacy and student life satisfaction among vocational high school students, with career decision self-efficacy (CDSE) as a mediator. Using a quantitative correlational design, 729 students from six vocational schools in Banda Aceh were selected through proportional stratified random sampling. Data were collected using the Career Search Self-Efficacy Scale (CSSES), the Career Decision Self-Efficacy Scale–Short Form, and the Student Life Satisfaction Scale, and analyzed using descriptive statistics and Sobel tests. The results are that career exploration efficacy, personal efficacy, and parental support positively influence CDSE and life satisfaction, whereas interview efficacy shows a negative effect due to anxiety. Mediation analysis confirms that CDSE significantly mediates the link between career search self-efficacy and life satisfaction, especially through self-appraisal and planning. The study extends Social Cognitive Career Theory by integrating cultural factors and highlighting the importance of school-based guidance in strengthening planning skills and family involvement. Keywords: career search self-efficacy, career decision self-efficacy, parental support, student life satisfaction, vocational high school